Identifying novel drugs with new modes of action for neglected tropical fungal skin diseases (fungal skinNTDs) using an Open Source Drug discovery approach. (3rd June 2022) - Lim, Wilson; Verbon, Annelies; van de Sande, Wendy
ABSTRACT: Introduction: The three fungal skin neglected tropical diseases (NTD) – mycetoma, chromoblastomycosis and sporotrichosis – currently lack prioritization and support to establish drug discovery programs in search for novel treatment options. This has made the efforts to identify novel drugs for these fragmented skinNTDs. Areas covered: To help escalate the discovery of novel drugs to treat these fungal skinNTDs, the authors have prepared an overview of the compounds with activity against fungal skinNTDs by analyzing data from individual drug discovery studies, including those performed on the Medicines for Malaria Venture (MMV) open access boxes. Expert opinion: The authors were unable to identify studies in which causative agents of all three skinNTDs were included, indicating that an integrated approach is currently lacking. From current available data, the azoles and iodoquinol were the only compounds with activity against causative agents from the three different fungal skinNTDs. Fungal melanin inhibition enhanced the activity of antifungal agents. For mycetoma, the fenarimols, aminothiazoles and benzimidazole carbamates are currently being investigated in the MycetOS initiative. To come to a more integrated approach to identify drugs active against all three fungal skinNTDs, compounds made in the MycetOS initiative could also be explored for chromoblastomycosis and sporotrichosis.